Micronutrient Alterations During Continuous Renal Replacement Therapy in Critically Ill Adults: A Retrospective Study. (18th December 2017) - Kamel, Amir Y.; Dave, Nisha J.; Zhao, Vivian M.; Griffith, Daniel P.; Connor, Michael J.; Ziegler, Thomas R.
Abstract: Background : Continuous renal replacement therapy (CRRT) is commonly used to provide renal replacement therapy in the intensive care unit. Limited published data suggest that CRRT may lead to depletion of water‐soluble vitamins and trace elements. The goal of this study was to identify the incidence of trace element and vitamin deficiencies in critically ill patients during CRRT. Materials and Methods : This study is based on a retrospective chart review of patients who were referred to Emory University Hospital's nutrition support services and had at least 1 serum micronutrient level measured during CRRT (thiamin, pyridoxine, ascorbic acid, folate, zinc, and copper) between April 1, 2009, and June 1, 2012. Results : Seventy‐five patients were included in the study. Nine of 56 patients (16%) had below‐normal whole blood thiamin concentrations, and 38 of 57 patients (67%) had below‐normal serum pyridoxine levels. Serum ascorbic acid and folate deficiencies were identified among 87% (13 of 15) and 33% (3 of 9) of the study patients, respectively. Nine of 24 patients had zinc deficiency (38%), and 41 of 68 patients had copper deficiency (60%). Of the 75 total subjects, 60 patients (80%) had below‐normal levels of at least 1 of the micronutrients measured. Conclusions : The incidence of various micronutrient deficiencies in critically ill patients who required CRRT was higher than previously reported. Prospective studies are needed to determine the impact of CRRT on micronutrient status and the potential clinical and metabolic efficacy of supplementation in the intensive care unit setting.